2018
DOI: 10.1159/000492179
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function and Autoimmune Indications in Patients with Anti-N-Methyl-D-Aspartate Receptor Encephalitis

Abstract: Objective: Previous studies have shown that functional abnormalities of the thyroid are associated with the pathogenesis of several neurological diseases. However, their relationship in patients with anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis remains to be defined. Methods: Forty-three patients with anti-NMDAR encephalitis were examined for thyroid function and autoimmune indications, in comparison with 225 healthy controls (CTL). Patients were further classified into 2 subgroups based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 36 publications
1
32
1
Order By: Relevance
“…Indeed, we observed that the fT3, but not fT4 or TSH, was signi cantly associated with poor functional outcome, and this effect remained signi cant after adjusting for age, gender, tumor presence and consciousness declination. Contrary to one former study (25.6%) 14 , our data didn't support the low T3 syndrome as a common nding in patients with anti-NMDAR encephalitis (6.25%), however, the relatively low fT3 value, although within the reference range, was associated with a poor functional outcome and might serve as a potential predictor of prognosis.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Indeed, we observed that the fT3, but not fT4 or TSH, was signi cantly associated with poor functional outcome, and this effect remained signi cant after adjusting for age, gender, tumor presence and consciousness declination. Contrary to one former study (25.6%) 14 , our data didn't support the low T3 syndrome as a common nding in patients with anti-NMDAR encephalitis (6.25%), however, the relatively low fT3 value, although within the reference range, was associated with a poor functional outcome and might serve as a potential predictor of prognosis.…”
Section: Discussioncontrasting
confidence: 99%
“…This constitutes the bases for evaluation of the potential association between thyroid hormones and the prognosis of anti-NMDAR encephalitis. To date, there are only a few data on this issue 13,14 , and its predictive value of functional outcome remains to be determined. Herein, we aimed to investigate the association between the thyroid hormones and functional outcome in patients with anti-NMDAR encephalitis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, anti-thyroid antibodies abnormalities and elevated complement levels are frequent in patients with anti-NMDAR encephalitis, which are associated with the short-term prognosis (7)(8)(9). Furthermore, in our present study, only 9 in 39 of anti-NMDAR encephalitis were positive for serum systemic autoantibodies (7 ANA, 1 ANCA, and 1 centromere antibody).…”
Section: Discussionsupporting
confidence: 57%
“…Previous reports have demonstrated the intertwining relationships between systemic immune abnormalities and immune-mediated neurological disorders, such as neuromyelitis optica spectrum disorder (NMOSD), and multiple sclerosis (5,6). Recently, several studies have revealed anti-thyroid antibodies abnormalities and elevated complement levels are frequent in patients with anti-NMDAR encephalitis, which are associated with the outcomes (7)(8)(9). Serum systemic autoantibodies that are indicative of systemic immune diseases, such as antinuclear antibodies (ANAs), extractable nuclear antigen autoantibodies (ENAs), rheumatoid factors (RFs), and anti-neutrophil cytoplasmic antibodies (ANCAs), have also been detected in patients with AE, but the literature in this regard is limited (8,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation